RANCANG BANGUN SISTEM INFORMASI RETENSI REKAM MEDIS DI RSIA X - Putri, Ramti Kania; Syahidin, Yuda; Hidayati, Meira (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2022)
This study aimed to design and create an outpatient medical record retention information system at The X Hospital. The results of research conducted, found several problems faced by the health center. It’s hard to find active and inactive medical record data, so the medical record data that are retained or inactive is unknown. The research method used is a qualitative approach that is supported by data collection techniques, using observation, interviews, and library research. The development method used is the waterfall method assisted by the design of Data Flow Diagrams. This system is based on a desktop that uses Microsoft Visual Studio 2010 as a programming language and uses the Microsoft Office Access 2013 database. Based on the problems above, the writer tries to give some suggestions, including (1) the Need development of information systems technology that the author will design. (2) Integration of health information systems to obtain efficient and effective performance.